Postprandial response of leptin and adiponectin to standardized high-carbohydrate and high-fat meals in adults: A cross-sectional study - Fabiola Mabel Del Razo-Olvera; Ana Teresa Arias-Marroquín; Mayra Martínez-Fajardo; Wendolyn Elideth Dávila-Olmedo; Ivette Cruz Bautista; Gabriela Alejandra Galán-Ramírez; Liliana Juárez-Martínez; Donají Verónica Gómez-Velasco; Luz Elizabeth Guillén-Pineda; Angelina López Estrada; Rodrigo Otero-Otero; Daniel Elías-López; et al. (PLoS ONE, 2026)
Background Leptin and adiponectin link adiposity with metabolic regulation. While their fasting levels have been extensively studied, little is known about their postprandial dynamics, and it is generally assumed that their concentration is unaffected by food intake. Objective To evaluate the postprandial responses of leptin and adiponectin following two standardized meals differing in macronutrient composition, in adults with and without obesity. Methods In 79 adults (43 women, 36 men; 47% with obesity), we investigated whether meal composition influences adipokine responses. Participants completed two standardized mixed-meal tolerance tests: a high-carbohydrate meal (60% carbohydrate, 20% fat, 20% protein) and a high-fat meal (50% fat, 30% carbohydrate, 20% protein). Blood samples were collected at baseline and after 60, 120, and 360 minutes. Data were evaluated using linear mixed-effects models. Results Women exhibited higher leptin and adiponectin concentrations than men (p < 0.001). Participants with obesity had higher leptin and lower adiponectin across all time points (p < 0.001) with both meals. In mixed-effects models, Sex and BMI were significant predictors of both concentrations of adipokines. Meal type significantly influenced leptin trajectories, with leptin concentrations having a progressive decline after the high-fat meal; in contrast, they did not change significantly after the high-carbohydrate meal. Adiponectin concentration showed only modest time-related changes but was not significantly modified by meal composition. Conclusions Sex and BMI are significant determinants of the postprandial dynamics of leptin and adiponectin, while meal composition, especially high-fat meals, influences leptin concentrations. These observations underscore the importance of considering postprandial dynamics rather than basal levels for assessing metabolic health. The reductions in leptin, particularly in individuals with obesity, could potentially influence satiety-related pathways, although this hypothesis requires confirmation in studies directly assessing appetite and energy intake.